2014
DOI: 10.1038/srep07061
|View full text |Cite
|
Sign up to set email alerts
|

SEPP1 gene variants and abdominal aortic aneurysm: gene association in relation to metabolic risk factors and peripheral arterial disease coexistence

Abstract: An inadequate selenium level is supposed to be a risk factor for cardiovascular diseases. However little is known about variation of the genes encoding selenium-containing proteins that would confirm the causality in these diseases. The aim of this study was to analyze the relationships between two functional variants of selenoprotein P gene (SEPP1 rs3877899G>A, rs7579G>A) and the occurrence of abdominal aortic aneurysm (AAA) and aortoiliac occlusive disease (AIOD), as well as their metabolic risk factors. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 47 publications
2
14
0
Order By: Relevance
“…These results indicate the partially distinct role of selenoproteins in the pathogenesis of aneurysmal and atherosclerotic ischemic types of arterial diseases, as well as their consequences, such as systolic HF. They confirm and extend our preliminary observation of the opposite role of the SEPP1 rs3877899A allele for the development of AAA with (a protective factor) and without (a risk factor) coexisting PAD [ 29 ]. The present study also focused on aortic diseases, but examined a larger number of selenoprotein genes in a larger sample of patients and controls (~50% increase).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…These results indicate the partially distinct role of selenoproteins in the pathogenesis of aneurysmal and atherosclerotic ischemic types of arterial diseases, as well as their consequences, such as systolic HF. They confirm and extend our preliminary observation of the opposite role of the SEPP1 rs3877899A allele for the development of AAA with (a protective factor) and without (a risk factor) coexisting PAD [ 29 ]. The present study also focused on aortic diseases, but examined a larger number of selenoprotein genes in a larger sample of patients and controls (~50% increase).…”
Section: Discussionsupporting
confidence: 88%
“…Finally, the correlations between selenoprotein levels and BMI values were analyzed, because in our previous study we found that the SEPP1 haplotype is a risk factor for AAA in overweight and obese subjects [ 29 ]. In AAA a negative correlation between the concentration of SeP and BMI was observed ( r = -.575, P < .0001, N = 60; Fig 2E ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Genes such as IRAK4 [61], albumin (ALB) [62] and plasminogen (PLG) [63] were involved in progression of CAD. Alteration in SEPP1 was important for development of peripheral arterial disease [64], but modification in this gene may be liable for advancement of CAD. Polymorphism in ALDH2 was liable for development of CAD [65].…”
Section: Discussionmentioning
confidence: 99%